Study of Ds1(2460)+→Ds+π+π- in B→D[bar](*)D+sπ+π- decays - Aaij, Roel; Bachmann, Sebastian; Carus, Leon; Caspary, Rowina; Celani, Sara; Cocha Toapaxi, Carlos; De Cian, Michel; Dittmann, Lucas; Esen, Sevda; Glaser, Fabian; Günther, Paul André; Han, Xiaoxue; et al. (Science bulletin, 2025)
An amplitude analysis of the Ds1(2460)+→Ds+π+π- transition is performed simultaneously in B0→D-Ds+π+π-, B+→D‾0Ds+π+π-, and B0→D*-Ds+π+π- decays. The study is based on a data sample of proton-proton collisions recorded with the LHCb detector at centre-of-mass energies of s=7,8, and 13TeV, corresponding to a total integrated luminosity of 9fb-1. A clear double-peak structure is observed in the m(π+π-) spectrum of the Ds1(2460)+→Ds+π+π- decay. The data can be described either with a model including f0500,f0980, and f2(1270) resonances, in which the contributions of f0(980) and f2(1270) are unexpectedly large, or with a model including f0(500), a doubly charged open-charm tetraquark state Tcs¯ and its isospin partner Tcs¯0. If the former is considered implausible, the Tcs¯ states are observed with high significance, and the data are consistent with isospin symmetry. When imposing isospin constraints between the two Tcs¯ states, their mass and width are determined to be (2327±13±13) MeV and (96±16-23+170) MeV, respectively, where the first uncertainty is statistical and the second is systematic. The mass is slightly below the DK threshold, and a spin-parity of 0+ is favoured with high significance.